x=5.54x+1= 2x+12-1 -14x=2x+11-2x -2x2x=11/2 /2x=5.5

2x + 2 = 4x -1 2x = 3 x = 1.5

If: 1-2x-5 = 4x+2 Then: -2x-4x = 2-1+5 And: -6x = 6 So: x = -1

Given, 4x2 - 4x + 3 = 0; then, 4x2 - 4x + 1 = (2x - 1)2 = -2, 2x - 1 = √-2 = ±i√2, and 2x = 1 ± i√2; therefore, x = ½(1 ± i√2).

4x + 1 = 2x + 5 4x + 1 - 2x = 2x + 5 - 2x 2x + 1 = 5 2x + 1 - 1 = 5 - 1 2x = 4 2x/2 = 4/2 x = 2

2x = 4x +1 2x-4x = 1 -2x = 1 x = - 1/2 check Leftside = 2 (- 1/2) = -1 Right side = 4 (- 1/2) +1 = -2 + 1 = 1 - 2 = -1 LS = RS therefore x = - 1/2

you want to put all of the 'x' on one side and all of the numbers on the other side 2x-5=4x-1 2x-5 (-2x +1) = 4x -1 (-2x + 1) -4 = 2x then divide by 2 x=-2

If: 2x+y = 1 then y = 1-2x and y^2 = (1-2x)^2 which is 1-4x+4x^2 If: x^2 -xy -y^2 = -11 then x^2 -x(1-2x) -(1-4x+4x^2) = -11 So it follows: x^2 -x +2x^2 -1 +4x -4x^2 +11 = 0 Collecting like terms: -x^2 +3x +10 = 0 Factorizing the above: (x-5)(-x-2) = 0 meaning x = 5 or -2 Points of intersection by substitution are at: (5, -9) and (-2, 5)

NOT CALCULUS. Use long division. 2x2 + x - 1(4x^4) 2x^2 goes into 4x^4 2x^2 times. The remainder will then be (2x^2*(x-1)). This result(2x^3 - 2x^2) is what need to be subtracted from 4x^4 to make it exactly divisible

If: 2x+y = 1 then y = 1-2x If: y^2 = (1-2x)^2 then y^2 = 1-4x+4x^2 If: x^2 +xy +y^2 =7 then x^2 +x(1-2x) +1-4x+4x^2 = 7 So it follows: x^2 +x-2x^2 +1-4x+4x^2 -7 = 0 Collecting like terms: 3x^2 -3x -6 = 0 Dividing all terms by 3: x^2 -x -2 = 0 Factorizing the above: (x+1)(x-2) = 0 meaning x = 2 or -1 By substitution points of contact are made at: (2, -3) and (-1, 3)

(x3 + 3x2 - 2x + 7)/(x + 1) = x2 + 2x - 4 + 11/(x + 1)(multiply x + 1 by x2, and subtract the product from the dividend)1. x2(x + 1) = x3 + x22. (x3 + 3x2 - 2x + 7) - (x3 + x2) = x3 + 3x2 - 2x + 7 - x3 - x2 = 2x2 - 2x + 7(multiply x + 1 by 2x, and subtract the product from 2x2 - 2x + 7)1. 2x(x + 1) = 2x2 + 2x2. (2x2 - 2x + 7) - (2x2 + 2x) = 2x2 - 2x + 7 - 2x2 - 2x = -4x + 7(multiply x + 1 by -4, and subtract the product from -4x + 7)1. -4(x + 1) = -4x - 42. -4x + 7 - (-4x - 4) = -4x + 7 + 4x + 4 = 11(remainder)

=2x2+x+4x+2=x(2x+1)+2(2x+1)=(2x+1)(x+2) by spaz licker enjoy slag ;)

(2x + 1)(2x + 1) or (2x + 1)2 so x = -0.5

4x2-4x-3 = 0 (2x-3)(2x+1) = 0 x = 3/2 or x = -1/2

0.5

Assuming there are no parentheses:2 times X - 1 + 4X - 6 + 2X =2X - 1 + 4X - 6 + 2X =2X + 4X + 2X - 1 - 6 =8X - 1 - 6 =8X - 7

We can solve this by following the steps I'm about to explain. 1) Write the equation out. â€¢ 4x + 1 = 2x - 3 2) Get the numbers and variables to their own side. â€¢ 4x + 1 = 2x - 3 â€¢ 4x + 1 - 1 = 2x - 3 - 1 â€¢ 4x = 2x - 4 â€¢ 4x - 2x = 2x - 2x - 4 â€¢ 2x = -4 3) Perform the opposite operation that is holding the variable together. (2x = 2(x) so we're multiplying - we need to divide) â€¢ 2x = -4 â€¢ 2x/2 = -4/2 â€¢ x = -2 4) Check your solution â€¢ 4x + 1 = 2x - 3 Substitute the value of X for every x in the equation. â€¢ 4(-2) + 1 = 2(-2) - 3 â€¢ -8 + 1 = -4 - 3 â€¢ -7 = -7

4x + 2 + 2x - 2x = 14 4x = 14 - 2 4x = 12 x = 3

As written, that's 2(x - 6) You may have meant 4x^2 - 2x - 12 which would be 2(2x + 3)(x - 2)

2x = 4x + 3 -2x = 3 x = -3 / 2

8x2-2x-3=0 (2x+1)(4x-3)=0 2x+1=0 or 4x-3=0 x=-1/2 or x=3/4

2x = x2 + 4x - 3 x2 + 2x - 3 = 0 (x - 1)(x - 2) = 0

y = 2x-5 4x-y = 7 => y = 4x-7 2x-5 = 4x-7 2x-4x = 5-7 -2x = -2 x = 1 Therefore by substituting: x = 1 and y = -3

Right, 3x-4x+9x-x1. 3x - x = 2x2. 9x-4x = 5x- 2x +5x = 7x

If: 2x+y = 1 Then: y = 1-2x If: x^2 + xy + y^2 = 7 Then: x^2 +x(1-2x) +(1-2x)^2 = 7 So: x^2 +x-2x^2 +1-4x+4x^2 -7 = 0 Collecting like terms: 3x^2 -3x -6 = 0 Divide all terms by 3: x^2 -x -2 = 0 Factorizing (x+1)(x-2) = 0 => x = -1 or x = 2 Solutions by substitution: (-1, 3) and (2, -3)

Trending Questions

What is 95 rounded to 90 or 100?

Asked By
Wiki User
What is the answer to100 x 0.05?

Asked By
Wiki User
What is 1.82 / 1.4 please help me?

Asked By
Orbs19
What is the difference between the highest and the lowest values Please someone help+3988 -19 -127 +1439 -356 -78 0?

Asked By
Derp Coco
Spaceship 1 and Spaceship 2 have equal masses of 300 kg. They collide. Spaceship 1's final speed is 2 ms and Spaceship 2's final speed is 1 ms in the same direction. What is their combined momentum?

Asked By
Wiki User
What does coefficient mean in math?

Asked By
Wiki User
When suzi stuck two lumps of coal in the snowmans face?

Asked By
Wiki User
a 1 in the tens place related to a 1 in the ones place?

Asked By
Mean Muth
Hottest Questions

How did chickenpox get its name?

Asked By
Wiki User
When did organ music become associated with baseball?

Asked By
Curt Eichmann
How can you cut an onion without crying?

Asked By
Leland Grant
Why don't libraries smell like bookstores?

Asked By
Veronica Wilkinson
How long will the footprints on the moon last?

Asked By
Daija Kreiger
Do animals name each other?

Asked By
Danika Abbott
Who is the longest reigning WWE Champion of all time?

Asked By
Consuelo Hauck
What was the first TV dinner?

Asked By
Roslyn Walter
Previously Viewed

What -1 -4x 2 2x x?

Asked By
Wiki User
Unanswered Questions

How many times does 10 go into 100?

Asked By
Wiki User
What times 2 equals 5?

Asked By
Wiki User
What number is greater 0.33 or 0.5?

Asked By
Wiki User
Why didn't Dexter want a pocket calculator?

Asked By
Wiki User
What is 162.5 rounded to the nearest tenth?

Asked By
Wiki User
What is 3 quarters of a meter?

Asked By
Wiki User
What is the remainder for 723 divided by 16?

Asked By
Wiki User
How many thirds in 4?

Asked By
Wiki User